2014
DOI: 10.1007/s00394-014-0676-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiotensin-converting enzyme by aqueous extract of tomato

Abstract: Together these data indicate that aqueous extract of tomatoes contain anti-ACE factors in addition to previously described anti-platelet factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…The mechanism of hypotensive effect of the extract is not fully explained. It is assumed, however, that it can reduce expression of renin and angiotensin-converting enzyme (ACE) [10]. Another mechanism through which STE can potentially lower BP is via an increase of the nitric oxide production, which subsequently leads to vasodilation [11].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of hypotensive effect of the extract is not fully explained. It is assumed, however, that it can reduce expression of renin and angiotensin-converting enzyme (ACE) [10]. Another mechanism through which STE can potentially lower BP is via an increase of the nitric oxide production, which subsequently leads to vasodilation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato juice was earlier shown to lower blood pressure in human volunteers, and this effect was thought to be associated with its high antioxidant content [99, 100]. We therefore tested whether Fruitflow ® inhibited human serum ACE activity and rabbit lung ACE activity [17]. The IC 50 value of Fruitflow ® for ACE inhibition in serum was 1.91 ± 0.24 mg/ml (0.038 μg catechin equivalent(CE)/ml), whereas for captopril, the value was 0.56 ± 0.08 μg/ml.…”
Section: New Functionalities Of Fruitflow®: Anti-inflammatory and Blomentioning
confidence: 99%
“…In a variety of studies, it was demonstrated that water-soluble components of tomatoes are capable of inhibiting platelet aggregation both in vitro and in vivo [1316]. These water-soluble tomato components were also found to inhibit angiotensin-converting enzyme (ACE) and to relax the vascular endothelium, the other important limbs of the cardiovascular system [17, 18]. A water-soluble tomato extract containing all the bioactive components was developed and later given the trade name Fruitflow ® .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that STE reduces the expression of cell adhesion molecules (ICAM-1, VCAM-1) in endothelial cells, which play an important role in the formation of atherosclerotic plaque [27]. Furthermore, there are reports describing the role of hypotensive properties of STE polyphenols in the mechanism of angiotensin-converting enzyme (ACE) inhibition [29]. In 2015, the guidelines of the Polish Society of Hypertension for the first time allowed the use of other substances (including STE) as alternatives to ASA.…”
Section: Standardized Tomato Extract In the Primary Prophylaxis Of Ismentioning
confidence: 99%